10 rules for dealing with police [videorecording (DVD)] - Whitmore, Rubin; Murphy, William H. (Flex Your Rights, 2010)
From simple misunderstandings to illegal searches and excessive force, a bad police encounter can happen to anyone. The film demonstrates how to handle various types of encounters with police and explains the rights of citizens in these situations.